Small-size Micro Processing System for Nanosatellite Separation. (2015) - Phylonin, Oleg; Gimranov, Zafar
Abstract: The principles of construction of small magnate-induction systems controlled microprocessor module to run the micro and nano-satellites to the specified path, with certain speeds. This is done by automatically selecting certain zenith and azimuth angles, by commands microprocessor regarding delivery vehicles.